Snake body size frequency distributions are robust to the description of novel species. Issue 5 (13th May 2016) - Maritz, Bryan; Kgaditse, Mimmie; Alexander, Graham John
Abstract: The accurate interpretation of body size frequency distributions (BSFDs) has important implications for understanding large‐scale ecological and evolutionary patterns because they are shaped by ecological and evolutionary processes. However, incomplete species sampling, resulting either from a paucity of reliable body size data or because those species have not yet been detected/described, also has the potential to influence BSFD shape and skew when missing species are disproportionately large or small. Missing species may thus influence the skew of a BSFD, misleading subsequent interpretations. In contrast to many vertebrate taxa, the BSFDs of snakes appears to be log‐normal, with no significant skew. However, the influence of imperfect species sampling on these distributions has however not been previously evaluated. We collated body size data and date of description for 300 species of elapid, and 264 species of viperid snakes and assessed the shape and skew of the BSFD of each clade. Next we tested the hypothesis that date of description was related to body size in each clade. We show that the BSFDs of elapid and viperid snakes are both log‐normal, with no significant skew. Moreover we demonstrate size‐related differences in the probability of detection (as measured by year of description) among elapids and vipers: in both lineages, species with larger body size tend to have been described earlier. However, simulations testing the effect of the addition of novel, small‐bodied species revealed that the distributions of elapids and vipers are not highly vulnerable to becoming significantly skewed in the future. Our results support current interpretations of BSFDs in snakes that suggest a lack of size‐associated biases in the speciation and extinction rates of this clade.